Physical analysis of peduncles of dwarf cashew clones for consumption, processed or natural - Galdino, Antonia Gorete da Silva; Ribeiro, Laiza Brito; Moura, Carlos Farley Herbster; Amorim, Francisca Frenna Verezza Rodrigues de; Innecco, Renato (Sociedad Colombiana de Ciencias Hortícolas-SCCH and Universidad Pedagógica y Tecnológica de Colombia-UPTC, 2019)
The physical characteristics of cashew-dwarf peduncles were evaluated to later indicate the best clones for natural consumption and/or processing, considering that consumers appreciate products for their visual attractiveness. The objective of this study was to analyze peduncles of dwarf cashew clones obtained from the Genetic Improvement Program of Embrapa Agroindústria Tropical, Cruz-CE experimental area, in order to make inferences about the physical characteristics and indicate the best clones for natural consumption and/or processing. The analyzed variables were: total mass of the cashew (MT), chestnut mass (MC), peduncle mass (MP), apical diameter (DA), basal diameter (DB), length and firmness. The experiment design was a randomized complete block design with 25 treatments (clones) with 3 replications and up to 12 cashews per plot (four plants in total). The analysis of variance and the comparison of the means by the Scott and Knott test was realized. When analyzing the MT values, it was found that 100% of the clones were classified as types 4 (approximately 150 g), 5 (approximately 100 g) and 6 (approximately 150 g) cashews/tray. As for MC, there was a variation from 8.18 to 15.08 g. General averages of 95.16, 50.07 and 41.38 mm were found for the variables length, DB and DA of peduncle, respectively. It is concluded that, in general, all clones presented good characteristics; however, clone 108-6 is the preference for most consumers since it has red staining, as did the control (CCP 76). Therefore, all clones presented desirable characteristics for natural consumption and/or processing.